2014
DOI: 10.1152/jn.00588.2013
|View full text |Cite
|
Sign up to set email alerts
|

Long-term in vivo time-lapse imaging of synapse development and plasticity in the cerebellum

Abstract: Synapses are continuously formed and eliminated throughout life in the mammalian brain, and emerging evidence suggests that this structural plasticity underlies experience-dependent changes of brain functions such as learning and long-term memory formation. However, it is generally difficult to understand how the rewiring of synaptic circuitry observed in vivo eventually relates to changes in animal's behavior. This is because afferent/efferent connections and local synaptic circuitries are very complicated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…This method produced sufficient pressure on the brain to reduce motion artifacts without causing clear signs of damage. In contrast, we found that additional pressure created by placing the coverslip inside the skull opening (Nishiyama et al 2014) or by putting agarose between the coverslip and brain (Hoogland et al 2015) caused damage to some PCs that became apparent over time (data not shown).…”
Section: Testing Gecis In Pcsmentioning
confidence: 78%
See 2 more Smart Citations
“…This method produced sufficient pressure on the brain to reduce motion artifacts without causing clear signs of damage. In contrast, we found that additional pressure created by placing the coverslip inside the skull opening (Nishiyama et al 2014) or by putting agarose between the coverslip and brain (Hoogland et al 2015) caused damage to some PCs that became apparent over time (data not shown).…”
Section: Testing Gecis In Pcsmentioning
confidence: 78%
“…These cerebellar regions are related to sensorimotor functions of the orofacial area including the tongue (Bryant et al , 2010Welsh et al 1995). Chronic imaging requires a stable, clear cranial window, a technique reported to be difficult in the mouse cerebellum (Nishiyama et al 2014). We found that three factors could help improve our success rate.…”
Section: Testing Gecis In Pcsmentioning
confidence: 89%
See 1 more Smart Citation
“…Dendritic spines are typically mushroom-shaped dendritic projections that are malleable, changing size and shape in response to activity and external cues. Such synaptic plasticity continues into adulthood and is associated with learning and memory (Chen et al, 2012; Hamilton et al, 2012; Holtmaat and Svoboda, 2009; Nishiyama et al, 2014; Trachtenberg et al, 2002). …”
Section: Introductionmentioning
confidence: 99%
“…This developmental transformation includes elimination and remodeling of existing synapses, commonly termed "synapse elimination," and is seen throughout the nervous system (1,2). Similar remodeling can occur throughout life during learning, aging, and disease, however (3)(4)(5).…”
mentioning
confidence: 99%